RECONSIDERING GLOBAL ENVIRONMENTAL GOVERNANCE coloniality, extractivism, and the pursuit of... environmental justice. - GODEK, WENDY (ROUTLEDGE, 2026)
Reconsidering Global Environmental Governance: Coloniality, Extractivism, and the Pursuit of Environmental Justice employs the concept of coloniality to examine the relationship between global environmental governance and environmental justice.Global environmental governance is perceived to be the natural solution for global environmental problems; however, its liberal emphasis reproduces colonial hierarchies at the expense of marginalized groups in the Global North and South alike. To develop this argument, this book draws on case studies that elucidate multiple expressions of coloniality in instances of socio-environmental conflict. With a focus on extractivism, the authors explore case studies in Greece and Honduras to illustrate the impact of existing global environmental governance institutions on marginalized groups and local communities, as well as case studies of gender and multispecies justice to highlight the opportunities and limitations of efforts to challenge liberal governance institutions and provide new pathways for enhancing environmental justice.Overall, the book aims to initiate a debate on how to decolonize global environmental politics and will be of particular interest to teachers, researchers, and students of environmental studies, global governance, development studies, political ecology, international political economy, and critical theory, as well as policymakers and civil society specialists.
Keywords: Environmental justice.; Environmental policy.; Political ecology.; Postcolonialism.; elektronické knihy; electronic books